Definição dos intervalos ótimos de manutenção preventiva de um laminador desbastador - Santana, Fabiano Candido (2019)
The reliability of each asset is already defined at the moment of its conception, that is, each equipment has a "DNA" depending on its design and assumptions. Thus, after the commissioning and in full operation, the scenarios change and the managers with their teams are challenged to maintain the high performance of these assets, but with new operating modes most of the time. This work will define the optimal intervals for preventive maintenance of an equipment, addressing some quantitative reliability engineering methodologies. Consisting of two phases, the first made the analysis of the systems that make up the Roughing Mill of ArcelorMittal Tubarão, showing a 98% availability with about 1,200 failures, allowing the selection of two more critical systems, the Horizontal Roughing Mill and the De-scaling Primary unit. That done, these two systems were detailed and reanalyzed at component level or LRU - Lowest Replaceable Unit. Thus, with RAM - Reliability, Availability and Maintenability analysis, the optimal preventive maintenance intervals of 115 LRU's were estimated, considering the basic tripod of cost, risk and performance.